Executive function influences sedentary behavior: A longitudinal study - Paul D. Loprinzi; Allison Nooe (Tabriz University of Medical Sciences, 2016)
Background: No study has evaluated the effects of executive function on follow-up sedentary behavior, which was this study's purpose. Methods: A longitudinal design was employed among 18 young adult college students (Mage = 23.7 years; 88.9% female). Accelerometer-determined sedentary behavior and physical activity, along with executive function, were assessed at baseline. Approximately 8 weeks later, re-assessment of accelerometer-determined sedentary behavior and physical activity occurred. Executive function was assessed using the Parametric Go/No-Go (PGNG) computer task. From this, 2 primary executive function outcome parameters were evaluated, including the Simple Rule and Repeating Rule. Results: After adjusting for baseline sedentary behavior, age, gender, body mass index and baseline moderate-to-vigorous physical activity (MVPA), for every 25% increase in the number of correctly identified targets for the Repeating rule at the baseline assessment, participants engaged in 91.8 fewer minutes of sedentary behavior at the follow-up assessment (β = -91.8; 95% CI: -173.5, -10.0; P = 0.03). Results were unchanged when also adjusting for total baseline or follow-up physical activity. Conclusion: Greater executive function is associated with less follow-up sedentary behavior.